Research of the butt joint steel sheet metal that is explosively cladded of nickel alloy Inconel 625 - Marcin Szmul (Przegląd Spawalnictwa, 2017)
The article presents a comparison of two welding technologies of butt joints of explosively cladded P355NH – Inconel 625 plate. The influence of applying pulsing current on the chemical composition of stitches made by method 131 is presented. The applied welding technology ensure the chemical composition in accordance with the requirements of ASME SECTION II, PART A and PN-EN 10095:2002.